Testing the inverseness of fertility and labor supply: the case of Ethiopia - Blen Solomon; Jean Kimmel (Institute for the Study of Labor (IZA), 2009)
We test the inverseness of fertility and labor supply for married women in Ethiopia to determine if previous research (focusing on developed countries) that has found an inverse relationship between fertility and labor supply is applicable to least developed countries. The research into fertility and labor supply has relied on a variety of methodologies for addressing the endogeneity of fertility. Using data from the Demographic Health Survey (DHS) of Ethiopia, we use the husband's desire for children to instrument for fertility. Our empirical results fail to support an inverse relationship between fertility and labor supply in Ethiopia, perhaps because the persistence of traditional family structures in the face of rising national female employment facilitates maternal employment. This finding has implications for other LDCs as well.
urn:nbn:de:101:1-20090209192
Keywords: J13; J22; 330; Labor supply; fertililty; Frauenerwerbstätigkeit; Arbeitsangebot; Fruchtbarkeit; Familiensoziologie; Äthiopien; Entwicklungsländer